2020
DOI: 10.1021/acs.chemrestox.0c00109
|View full text |Cite
|
Sign up to set email alerts
|

Gene–Environmental Interplay in Bisphenol A Subchronic Animal Exposure: New Insights into the Epigenetic Regulation of Pancreatic Islets

Abstract: Endocrine-disrupting chemicals (EDCs) such as bisphenol A (BPA), which is widely used in the plastic industry, have recently been considered to be involved in the pathogenesis of metabolic disorders, including obesity and diabetes. The present study aimed to examine the potentially detrimental effects of BPA on glucose and energy metabolism at the epigenetic level. The blood glucose profile of Wistar rats receiving different oral doses of BPA over 28 days was assessed. At the end of the treatment, the islets o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…62 An explanation for this phenotype is that epigenetic modifications of PDX-1, including both increased DNA methylation and histone modifications, are associated with reduced gene transcription in rat islets. 62,[101][102][103] Collectively, all these studies evidently support a crucial role of epigenetic modification of PDX-1 in the occurrence and development of T2DM.…”
Section: Changes In Pdx-1 Methylation Status Are Related To Diabetesmentioning
confidence: 55%
See 1 more Smart Citation
“…62 An explanation for this phenotype is that epigenetic modifications of PDX-1, including both increased DNA methylation and histone modifications, are associated with reduced gene transcription in rat islets. 62,[101][102][103] Collectively, all these studies evidently support a crucial role of epigenetic modification of PDX-1 in the occurrence and development of T2DM.…”
Section: Changes In Pdx-1 Methylation Status Are Related To Diabetesmentioning
confidence: 55%
“…[98][99][100] An increase in the methylation at the PDX-1 site reduces the expression of PDX-1 protein in the islets which has been confirmed in the model of T2DM rats. 101 Previous studies have shown that an adverse intrauterine environment leads to reduced pancreatic PDX-1 expression and hence impaired insulin secretion and diabetes in adult rats. 62 An explanation for this phenotype is that epigenetic modifications of PDX-1, including both increased DNA methylation and histone modifications, are associated with reduced gene transcription in rat islets.…”
Section: Changes In Pdx-1 Methylation Status Are Related To Diabetesmentioning
confidence: 99%
“…Several studies have demonstrated that bisphenols are related to several pathological conditions such as endocrine disorders, type II diabetes, reproductive system disorders, cancer (Rahmani, 2020. Accordingly, it was claimed that BPA reduces daily sperm production and causes infertility (Geens, 2012, Gerona, 2013, Aris, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Mcllwraith et al recently demonstrated that miR-708-5p mediates the effects of BPA in hypothalamic cells through the reduction of neuronatin levels and the increase in orexigenic Neuropeptide (Npy) [78]. Contrarily, Rahmani et al showed revealed that the expression of miR-375, miR-676, miR-126-a, and miR-340-5p was significantly disrupted by BPA, resulting in aberrant β-cell metabolism and diabetes [79]. More interestingly, the interplay between environment and gene expression seems to be a coordinated action of different ncRNA biotypes, at least lncRNAs and miRNAs.…”
Section: Pollution Impact On Ncrnasmentioning
confidence: 99%